2009
DOI: 10.1002/anie.200806111
|View full text |Cite
|
Sign up to set email alerts
|

A Total Synthesis of Norhalichondrin B

Abstract: Keywords natural products; pyrans; polyethers; metathesisThe halichondrin family of marine polyethers, first defined by the isolation and structure elucidation of norhalichondrin A by Uemura and co-workers in 1985, now numbers ~ 15 compounds.[1] The structures of the halichondrins, as exemplified by norhalichondrin B (Figure 1) are characterized by a 53-55 carbon backbone that is defined by two domains: the spiroketal containing C31-C53/55 region and a C1-C30 macrolactone that also contains a 2,6,9-trioxatricy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…Recently, this approach has been exploited in the synthesis of norhalichondrin B 235 [126] (Scheme 57). Additionally, an oxa-Michael strategy has been used by Brimble et al [127] for the synthesis of bis(benzannulated)-spiroacetals 238 (Scheme 58).…”
Section: Oxa-michael Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, this approach has been exploited in the synthesis of norhalichondrin B 235 [126] (Scheme 57). Additionally, an oxa-Michael strategy has been used by Brimble et al [127] for the synthesis of bis(benzannulated)-spiroacetals 238 (Scheme 58).…”
Section: Oxa-michael Cyclizationmentioning
confidence: 99%
“…Wulff et al [131] have reported a tandem desymmetrization/oxa-Michael addition in their studies toward the spiroacetal Scheme 57 Oxa-Michael approach towards norhalichondrin B [126] portion of didemnaketal A (Scheme 60). Sharpless asymmetric dihydroxylation of the meso bis-enone 248 and in situ hemiacetalization followed by conjugate addition gave the singly anomeric spiroacetal 251 as the only product.…”
Section: Oxa-michael Cyclizationmentioning
confidence: 99%
“…45 The overall plans for the synthesis are summarized in Figure 9. The completion of the synthesis was planned around a late-stage HornerWadsworth-Emmons coupling of C1-C39-containing phosphonate 149 with the C40-C53 domain aldehyde 147, followed by spiroketal formation.…”
Section: Total Synthesis Of Norhalichondrin B By Phillips and Co-workersmentioning
confidence: 99%
“…Moreover, the same authors have reported the total synthesis of the biologically active natural product norhalichondrin B, which also involved a domino ring-opening-ring-closing metathesis of a chiral highly functionalised ether under very similar conditions, providing the corresponding chiral key pyranopyran in 71% yield, as shown in Scheme 1.58. 96 A novel asymmetric approach to a densely functionalised lactarane skeleton in enantiomerically pure form, involving a domino ring-opening-ring closing metathesis of a chiral norbornene derivative, was reported by Ghosh et al, in 2008. 97 As shown in Scheme 1.59, the reaction of a chiral auxiliary with ethylene in the presence of a first-generation Grubbs' catalyst afforded the corresponding enantiopure hydroazulene derivative in 65% yield as a single product.…”
Section: Ruthenium-catalysed Domino Reactionsmentioning
confidence: 99%